MOLECULAR IDENTIFICATION AND GENOTYPING OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) IN DIFFERENT CLINICAL SAMPLES - Taher, Fatma S.; Othman, Hemin E. (Science Journal of University of Zakho, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a serious human pathogen that can spread in healthcare facilities and among the general public. This study was aimed to evaluate the prevalence and diversity of SCCmec types of this superbug among hospitalized patients. This study involved phenotypic identification and molecular confirmation of S. aureus based on the nuc gene, molecular detection of MRSA, SCCmec typing, and virulence factor profiling of MRSA clinical isolates obtained from hospitalized patients in Duhok province. Out of the 310 enrolled patients, 33 isolates (10.64%) were identified and confirmed as Staphylococcus aureus, of which 51.5% were identified as MRSA based on phenotypic and molecular targeting of the mecA gene. There were no discernible variations between the prevalence rates of this pathogen in different clinical sources, sexes, or age groups (p-values: 0.71, 0.39, and 0.15 respectively). The isolates had elevated rates of resistance to most antibiotic classes. They were classified as extensive drug-resistant (30.3%), multidrug-resistant (57.5%), and non-multidrug-resistant (12.1%). Additionally, SCCmec typing of MRSA by multiplex PCR identified three different SCCmec types and subtypes, including SCCmec type II (35.5%), followed by 17.64% of SCCmec type IV subtype d (IVd), and SCCmec type III (11.76%). However, 35.3% of the MRSA isolates were found to be non-typeable. Molecular profiling of major virulence factors and toxin genes revealed that 57.5% of the isolates were positive for the exfolitative toxin (ETA), 45.4% of the isolates carried TSST-1 (Toxic Shock Syndrome Toxin-1), the PVL (Panton-Valentine Leukocidin) cytotoxin was identified in 15% of the isolates, and 18.1% of the identified S. aureus isolates were positive for the ACME (arginine catabolic mobile element). The findings of the current investigation pointed out the circulating of highly virulent and extensively resistant MRSA strains among hospitalized patients, which may require active surveillance and better control policies